Pengembangan Perangkat Pembelajaran Model Generatif Untuk Meningkatkan Hasil Belajar Fisika Peserta Didik - Nyena Efendi; Gunawan Gunawan; Ahmad Busyairi (Department of Physics Education, Universitas Mataram, 2022)
The purfose of this study is to determine the feasibility of the learning tools based generative. This type of research is research and development that refers to a 4-D model which consists of four stages of development, namely define, design, develop and disseminate. The learning tools developed in this research are syllabus, RPP, teaching materials, LKPD, and cognitive learning outcomes test instruments. This research is limited to the content and construct validation stage of learning devices. Validation is carried out by the validator using a validation test instrument in the from of a questionnaire. The results of the validation of learning tools in the form of syllabus, RPP, teaching materials, LKPD, and cognitive learning outcomes test instruments werw obtained in the valid category. Based on the results and discussion of this research, it can be concluded that the learning tools developed are suitable for us in high school physics learning activities.